S100A12 and the S100/Calgranulins: Emerging Biomarkers for Atherosclerosis and Possibly Therapeutic Targets. Issue 12 (December 2015) - Oesterle, Adam; Hofmann Bowman, Marion A.
Abstract : Atherosclerosis is mediated by local and systematic inflammation. The multiligand receptor for advanced glycation end products (RAGE) has been studied in animals and humans and is an important mediator of inflammation and atherosclerosis. This review focuses on S100/calgranulin proteins (S100A8, S100A9, and S100A12) and their receptor RAGE in mediating vascular inflammation. Mice lack the gene for S100A12, which in humans is located on chromosome 3 between S100A8 and S100A9. Transgenic mice with smooth muscle cell–targeted expression of S100A12 demonstrate increased coronary and aortic calcification, as well as increased plaque vulnerability. Serum S100A12 has recently been shown to predict future cardiovascular events in a longitudinal population study, underscoring a role for S100A12 as a potential biomarker for coronary artery disease. Genetic ablation of S100A9 or RAGE in atherosclerosis-susceptible apolipoprotein E null mice results in reduced atherosclerosis. Importantly, S100A12 and the RAGE axis can be modified pharmacologically. For example, soluble RAGE reduces murine atherosclerosis and vascular inflammation. Additionally, a class of compounds currently in phase III clinical trials for multiple sclerosis and rheumatologic conditions, the quinoline-3-carboxamides, reduce atherosclerotic plaque burden and complexity in transgenic S100A12 apolipoprotein E null mice, but have not been tested with regards to human atherosclerosis. The RAGE axis is an important mediator for inflammation-induced atherosclerosis, and S100A12 has emerged as biomarker for human atherosclerosis. Decreasing inflammation by inhibiting S100/calgranulin-mediated activation of RAGE attenuates murine atherosclerosis, and future studies in patients with coronary artery disease are warranted to confirm S100/RAGE as therapeutic target for atherosclerosis.